Procedural norms in the system of procedural law: general theoretical aspect - Атаманчук, Ірина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Based on the distinguishing of particular system qualities, the concept, content, features of procedural rules are studied in the article, the development dynamics of the operating rules of the system of national procedural law is analized. It’s concluded that there is a unity of procedural rules and the ways of their settlement, which states the need of substantive norms’ implementation. After the criterion of dependence of character of legal relationships, which are regulated by legal norms, there are substantive norms and procedural (norms of judicial right). Substantive legal norms are determined by right and duties of participants of legal relationships, and judicial norms determine the order of realization of rights and duties, set substantive legal norms. Judicial legal norms play an essential role in providing of optimum terms of the legal adjusting, carry the basic loading of normative method of providing of legality, guaranteing the defence of rights, freedoms and legal interests of citizens. It is clear that it is impossible today to draw conclusion about democracy of the legal system only on the maintenance of the substantive fields of law, it is necessary to analyse the proper judicial norms which provide realization of substantive norms. Norms of domestic judicial right are the primary element of construction of the system of judicial right, they belong to the different fields and differ in the character of providing substantive legal relations, mostly have stable maintenance and setting, and in their complex they should be examined as an integral dynamic system. At all social meaningfulness of judicial right it is impossible not to define the certain underestimation of role of judicial norms in legal literature. In a certain measure it is inherently to the general theory of the state and right, as traditionally judicial norms were probed only within the framework of a particular branch sciences, but not within the framework of general theory of the state and right, that is why a general theoretic analysis of judicial norms in the system of judicial right for Ukraine is actual for modern legal science. The purpose of the scientific article is a general theoretic analysis of judicial norms in the system of judicial right for Ukraine, by the selection of system properties of judicial norms. The components of the system of judicial right - to separate judicial norms - are examined in the article. As a result of analysis of judicial norms, an author grounds a conclusion about similarity of their system of properties, conditioned community in the specific of setting.